Kompetencja Rzecznika Finansowego do nakładania kar pieniężnych na podmioty rynku finansowego - Wyżykowski, Bartosz (Studia Prawa Publicznego, 2018)
The subject of this article is the competence of the Financial Ombudsman to impose financial penalties on financial market entities for violations of the provisions of the Act of 5 August 2015 on complaints handling procedures by financial market entities and on the financial Ombudsman. One of the main tasks of the Financial Ombudsman is to enforce the proper performance by financial market entities of their obligations under the Act. For this purpose, Article 32(1) thereof provides that in the event of a breach of the provisions set out in the Act the Financial Ombudsman may, by way of a decision, impose a fine of up to PLN 100 000. The short duration of the new provisions and, consequently, the lack of case law outlining the directions of their interpretation may, particularly in the initial period, give rise to doubts as to their application. The aim of the article is to analyse possible disputable issues and provide proposals for their resolution. In particular, it is necessary to discuss the conditions for imposing a fine on a financial market entity. In this regard it is important to analyse both – the specific torts indicated in Article 32(1) of the said Act, as well as the general rules upon which the imposition of administrative fines by the Financial Ombudsman is possible. Also important is the consideration of the rules for determining the amount of the fine and in this matter the mutual relationship between Article 32 and the provisions of section IVa of the Act of 14 June 1960. Finally, amendments to certain provisions of the exiting laws are being proposed in order to increase the effectiveness of actions undertaken by the Financial Ombudsman and consequently to increase the level of protection of clients of financial market entities.